Research Progress on Regulatory T Cells in Acute Kidney Injury - Yamei Wang; Yuhong Tao (Journal of Immunology Research)
Immune inflammation is crucial in mediating acute kidney injury (AKI). Immune cells of both the innate and adaptive immune systems substantially contribute to overall renal damage in AKI. Regulatory T cells (Tregs) are key regulator of immunological function and have been demonstrated to ameliorate injury in several murine experimental models of renal inflammation. Recent studies have illuminated the renal-protective function of Tregs in AKI. Tregs appear to exert beneficial effects in both the acute injury phase and the recovery phase of AKI. Additionally, Tregs-based immunotherapy may represent a promising approach to ameliorate AKI and promote recovery from AKI. This review will highlight the recent insights into the role of Tregs and their therapeutic potential in AKI.